The influence of factors associated with past reproductive histories on migraines in middle-aged premenopausal women: a nationwide population-based study in Republic of Korea - Kim, Seonghoon; Na, Seunghee; Kim, Young-Do; Bae, Dae Woong; An, Jae Young; Park, Jeong Wook (Frontiers in Neurology, 2024)
Introduction Women can experience various reproductive events, such as pregnancy, childbirth, lactation, and contraception, which cause long-term changes in female hormones. In middle-aged women, the prevalence of migraine is high, and a clear gender difference is evident. This study investigated the effects of factors associated with past reproductive events on the risk of new migraine in middle-aged premenopausal women. Methods The influence of reproductive factors on migraine in middle-aged women was investigated using the Korean National Health Insurance Service (KNHIS) and Korean Health Examination (KHE) databases. The reproductive factors of interest were parity, breastfeeding, and oral contraceptive (OC) use. The study included 949,704 middle-aged premenopausal women 40–60 years of age. The study population was divided into two groups based on new diagnosis of migraine during the follow-up period (2009–2018). Results The risk of new migraine tended to increase in the primiparous (hazard ratio, HR: 1.179; 95% confidence interval, CI: 1.137–1.221) and multiparous groups (HR: 1.181; 95% CI: 1.142–1.221) compared with the nulliparous group. The breastfeeding ≥12 months group (HR: 1.071; 95% CI: 1.052–1.091) showed a significantly increased risk of new migraine compared with the non-breastfeeding group. All women in the OC groups (< 1 year, HR: 1.048; 95% CI: 1.028–1.069 and ≥ 1 year, HR: 1.100; 95% CI: 1.067–1.134) showed a higher risk of new migraine than those in the non-OC group. Conclusion The results of the current study indicate that childbirth, longer breastfeeding, and OC use may be associated with a higher risk of new migraine in middle-aged premenopausal women.